2011
DOI: 10.1017/s2078633610000962
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary screening of genetic lineage of Nigerian local chickens based on blood protein polymorphisms

Abstract: Blood samples for blood protein analysis were collected from three strains of the Nigerian local chicken (normal feathered, frizzle feathered and naked neck) and one exotic strain (Anak Titan). Each of these populations represents a genotype. Blood samples from 50 birds per genotype were used to assess genetic diversity of the Nigerian local chickens. A total of 18 bands were observed from the four strains during resolution of the proteins using sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
1
5
2
Order By: Relevance
“…In other words, the Normal feather and Frizzle feather populations were probably closely related to each other than the Naked Neck population which was found in a separate sub-clade. Interestingly, this result supported reports from previous studies that used different microsatellite markers (Ohwojakpor et al, 2012) and biochemical markers (Adeleke et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…In other words, the Normal feather and Frizzle feather populations were probably closely related to each other than the Naked Neck population which was found in a separate sub-clade. Interestingly, this result supported reports from previous studies that used different microsatellite markers (Ohwojakpor et al, 2012) and biochemical markers (Adeleke et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…The lines belonging to the Pirbright Institute are inbred chickens that have been housed in sterile conditions only for laboratory use (Additional file 1: Table S1). The Nigerian and Ethiopian samples are indigenous chickens from small villages and grown in captivity [9]. The Nigerian indigenous chickens are left to roam in the village, feed from picking earthworms, insects, herbage, household refuse, crop residues, seeds from the ground or in farms and return in the evening to their enclosures.…”
Section: Methodsmentioning
confidence: 99%
“…The authors also inferred that the YE IC populations were still under natural selection. Adeleke et al [104] had reported mean genetic similarity index of 55% between normal feathered, frizzle feathered and naked neck IC genotypes using blood protein polymorphisms and inferred clearly separated genotypes with naked neck genotype being the most diverged.…”
Section: Genetic Diversity and Distance Within And Between Ecotypes And Genotypesmentioning
confidence: 99%